Studi Intersepsi Hujan pada Hutan Tanaman Eucalyptus Pellita di Riau - Agung Budi Supangat; Putu Sudira; Haryono Supriyo; Erny Poedjirahajoe (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2012)
The aim of this study is to know the magnitude of rainfall interception loss in E. pellita plantation forest, at PerawangRiau. In order to obtain the magnitude of interception loss, stemfl ow and throughfall were measured on E. pellita plants at ages of 2 to 6 years with replication of 3 times, respectively. The results showed that the magnitudes of interception loss, throughfall and stemfl ow were 13.3-18.7 %; 7.7-83.1 % and 3.6-4.1 % from rainfall, respectively. The canopy storage capacity was calculated at 0.8 mm. The relationships of rainfall against both throughfall and stemfl ow showed strong correlations with r2 values of 0.99 and 0.79, respectively; while rainfall against interception has moderate correlation with r2 value of 0.58.ABSTRAKPenelitian ini bertujuan untuk mengetahui besarnya kehilangan air melalui intersepsi di hutan tanaman E. pellita, di Perawang-Riau. Untuk menghitung besarnya nilai intersepsi, dilakukan pengukuran aliran batang (stemfl ow) dan lolosan tajuk (throughfall) pada umur tanaman 2, 3, 4, 5, dan 6 tahun, masing-masing 3 ulangan pohon. Hasil penelitian menunjukkan besaran kisaran nilai intersepsi, throughfall dan stemfl ow masing-masing 13,3-18,7 %; 7,7-83,1 % dan 3,6-4,1 % dari curah hujan. Kapasitas tampungan tajuk (canopy storage capacity) tanaman E. pellita rata-rata sebesar 0,8 mm. Hubungan curah hujan dengan throughfall dan stemfl ow menunjukkan korelasi yang kuat (r2 rata-rata 0,99 dan 0,79), sedangkan dengan intersepsi korelasinya kurang kuat (r2 rata-rata 0,58).